The 2009 Swine-Origin H1N1 Influenza Virus and Its Implications to Public Health - Lu, MD, PhD, MHA, Shan (North American Journal of Medicine and Science, 2010)
The major public health event in 2009 is the outbreak of a new influenza virus infection in almost every region of the world. Because the original source of this virus was pigs, this virus was named “Swine-Origin Influenza A (H1N1) Virus (S-OIV)” in leading medical journals such as the New England Journal of Medicine. However, due to concerns regarding the potential for a misunderstanding that would lead the public to blame pigs for the outbreak as was the case in some Mideast countries where the national slaughter of pigs was started shortly after the outbreak, the World Health Organization (WHO) renamed the virus as “Type A H1N1 Influenza Virus”, which has generated significant confusion not only among the general public but also among healthcare professionals.